Estrategia de asociatividad para la comercialización de cacao en los distritos de Lamas y Chazuta de la región de San Martín - Montenegro Mantilla, Raúl Rodrigo Emmanuel (2021)
The associativity as a development mechanism to improve the lifestyle of farmers is a strategy that not only benefits this economic group, but also the community as a whole. This research aims to document the benefits of choosing this type of collectivity in order to follow the main objective, which seeks to explain that the commercialization of cacao through the associativity strategy has a positive impact on the price of cacao beans in the districts of Lamas and Chazuta. The research questions are solved through primary sources as a result from surveys and interviews to the farmers inside or outside a cooperative from the above-mentioned districts. This investigation shows that more than 70% of the surveyed farmers have a grow room of 2 to 4 ha. However, farmers do not use all the field to cultivate cacao, they also use it for other agricultural activities. Furthermore, the research also shows that most producers sells the kg of grain between 6 and 7 soles for associates, but for non-associated farmers the price per kilo ranges from 5 to 6, which represents a difference between associated and non-associated farmers. To conclude, it is appropriate for the farmers to choose an associative model that allows them to meet their basic needs, such as the highest selling price, the safe sale, the expansion to the international market, among other elements.